MEMBANGUN SEMANGAT KEWIRAUSAHAAN DALAM PENGELOLAAN SAMPAH DI DESA JATI KECAMATAN CIPUNAGARA KABUPATEN SUBANG - -, Hendra; Purnomo, Margo (Universitas Padjadjaran, 2016)
The result of the identification is done through observation , interviews and recommendations KKNM students showed that the problems that arise in the village of Jati subdistrict Cipunagara Subang Regency is the issue of waste management . Through extension and advisory team is working to increase public awareness, especially in enacting the trash , build entrepreneurial spirit in managing waste and the establishment of waste management . The monitoring results show that the waste management inÂ the village of Jati subdistrict Cipunagara begin to be realized although only up to the stage of increasing awareness of the public to dispose of waste in TPS and effort waste management in realizing the implementation of waste management through socialization, manufacture garbage bins, attempt of procurement and transportation of garbage , and the source setup power waste manager .